Antiquity and capitalism: The finance-growth perspective - Akos Dombi; Theocharis Grigoriadis; Junbing Zhu (Freie Universität Berlin, School of Business & Economics, 2020)
This paper explores the impact of antiquity on capitalism through the finance-growth nexus. We define antiquity as the length of established statehood (i.e., state history) and agricultural years. We argue that extractive institutions and deeply entrenched interest groups may prevail in societies with ancient roots. The paper offers an in-depth analysis of one particular channel through which extractive institutions may impair economic growth: the finance-growth channel. We propose that in countries with ancient statehood, the financial sector might be captured by powerful economic and political elites leading to a distorted finance-growth relationship. We build a model in which the equilibrium relationship between companies and banks depends on the entrenchment of the economic elites and the length of established statehood. To validate our argument empirically, we run panel-threshold regressions on a global sample between 1970 and 2014. The regression results are supportive and show that financial development - measured by the outstanding amount of credit - is negative for growth in states with ancient institutional origins, while it is positive in relatively younger ones.
urn:nbn:de:kobv:188-refubium-27492-7
Keywords: C70; N20; O16; O17; O47; 330; antiquity; finance-growth nexus; interest groups; rent-seeking